Using Videoconferencing Focus Groups in Sexual and Reproductive Health Research With Chinese Im/Migrants in Australia. (December 2021) - Wong, Horas T. H.; Jin, Defeng; Wang, Pan; Sun, Yingli; Mao, Limin; Zhang, Ye; Ogilvie, Erin; Vujcich, Daniel; Newman, Christy; O'Connor, Catherine C.; Vaughan, Cathy; Carter, Allison
Videoconferencing focus groups have emerged as a popular method for collecting qualitative data. However, its use in sexual and reproductive health research is still very much in its infancy. Based on participants' feedback and researchers' reflections on using videoconferencing focus groups to collect sexual and reproductive health data with 39 heterosexual and non-heterosexual Chinese im/migrants in Australia, we discuss some of the key lessons learned, and considerations involved in shifting from face-to-face to online focus groups. Overall, videoconferencing focus groups appeared to be a highly feasible and acceptable way to discuss "sensitive" topics with Chinese im/migrants. Importantly, researchers need to be both creative and reflexive during the research process and must not forget that the success of a study lies not only in troubleshooting technical issues but also in cultivating and maintaining a trusting relationship with research participants.